Pengembangan Sistem Informasi Manajemen Pelaporan Prakerin (Praktik Kerja Industri) (Studi Pada SMK Negeri 5 Malang) - Rendy Murdiyanto; Satrio Hadi Wijoyo; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Industrial work practice is a form of organizing vocational secondary education in order to create a professional workforce in their field. SMK Negeri 5 has collaborated with several industry parties, in order to assist students in carrying out internship activities to the maximum. However, in the implementation of prakerin there are existing problems such as the management of prakerin which is still manual and still in hard copy, the collection of journal forms for internship activities at the end of the prakerin, that leads the supervising teacher unable to monitor and guide students' prakerin activities optimally and the supervising teacher does not know the activities of the students on a daily basis. Based on the existing problems, this study developed a management information system for prakerin reporting at SMK Negeri 5 Malang. This research uses the SDLC (System Development Life Cycle) method, namely the Waterfall model, this research is also only limited to the testing stage not to the product maintenance stage. The analysis of system requirements using the interview method. From the interview results obtained 3 (three) users, namely, admin, teacher, and students with 17 functional requirements that exist in the system. At the implementation stage of the information system using web-based programming languages ​​such as PHP, HTML, Javascript, CSS and using the Laravel Framework. At this stage of the testing process using the Black-box testing method and User Acceptance Testing (UAT). Based on the results of the Black-box test, the results show that the functional requirements are 100% valid, while the User Acceptance Testing (UAT) test results in a percentage of 86.66%, so the system is declared to be running smoothly and can be used properly.